Membrane trafficking in neurodevelopmental disorders – new insight and therapeutic implications - Pawłowicz, Małgorzata (Journal of Education, Health and Sport, 2024)
Introduction: Membrane trafficking processes are essential for cell viability and basic functions, as well as for interactions between the cell interior and the surrounding environment. Purpose: This article focuses on the review of specific subgroup of inherited neurodevelopmental disorders caused by membrane trafficking dysfunction. The possibility of innovative therapeutic approaches based on selective effects on membrane trafficking processes is also discussed. State of knowledge: Most previously published reviews are lists of multi-organ diseases related to membrane trafficking dysfunction that are grouped by damaged genes/proteins or by single dominant clinical symptom. No review that focused exclusively on the subgroup of neurodevelopmental diseases related to membrane trafficking defects and their differential diagnosis useful in clinical practice, could be identified. Conclusions: Neurodevelopmental diseases related to membrane trafficking defects constitute a significant still growing group of rare/ultra-rare disorders which, due to the spectrum of symptoms, require differentiation from the more common neurogenetic syndromes with different pathomechanisms of the disease, but also related to intellectual disability, autism, epilepsy or neurodegenerative processes. The design of innovative drugs based on selective effects on membrane trafficking processes creates wide opportunities for precise, targeted therapeutic intervention, with a significantly minimized risk of its ineffectiveness or side effects.